CIVIL LIABILITY FOR AFFECTIVE AND MATERIAL ABANDONMENT: JURISPRUDENTIAL EVOLUTION AND THE PROTECTION OF HUMAN DIGNITY (REMUNOM, 2026)
Civil liability for affective and material abandonment has gained prominence in contemporary Law, particularly in light of the increasing recognition of human dignity within family relationships. This study aims to analyze the jurisprudential evolution of civil liability in such cases, as well as the criteria adopted for its application in the Brazilian legal system. It is a qualitative research developed through a literature review, based on recent scientific articles addressing the topic from doctrinal and jurisprudential perspectives. The findings indicate that civil liability is not grounded in the imposition of affection, but rather in the violation of the legal duty of care, requiring the demonstration of elements such as relevant omission, actual damage, and causal link. Furthermore, human dignity emerges as a central principle in judicial reasoning, although divergences remain regarding the extent and limits of legal intervention in family relations. It is concluded that, despite significant advances, more objective criteria are still needed to ensure legal certainty and consistency in judicial decisions.